MCEND: an open-source program for quantum electron-nuclear dynamics - Ulusoy, Inga; Aebersold, Lucas E.; Wang, Cong; Wilson, Angela K. (Computer physics communications, 2025)
The software MCEND (Multi-Configuration Electron-Nuclear Dynamics) is a free open-source program package which simulates the quantum dynamics of electron-nuclei simultaneously for diatomic molecules. Its formulation, implementation, and usage are described in detail. MCEND uses a grid-based basis representation for the nuclei, and the electronic basis is derived from standard electronic structure basis sets on the nuclear grid. The wave function is represented as a sum over products of electronic and nuclear wave functions, thus capturing correlation effects between electrons, nuclei, and electrons and nuclei. The LiH molecule was used as an example for simulating the molecular properties such as the dipole moment and absorption spectrum. PROGRAM SUMMARY Program Title MCEND, v.2.6.0 CPC Library link to program files: https://doi.org/10.17632/tkb9dwf85t.1 Developer's repository link: https://github.com/MCEND-hub/MCEND (https://github.com/MCEND-hub/MCEND-library and https://github.com/MCEND-hub/MCEND-tools are git submodules of MCEND) Licensing provisions: MIT Programming language: Fortran 90 and Python 3 External routines/libraries: FFTW, OpenMP, BLAS, LAPACK, PSI4, Matplotlib, mendeleev, NumPy, Pandas, SciPy, PyTables Nature of problem: MCEND is to simulate the quantum dynamics of electrons and nuclei simultaneously at multiconfiguration levels. Solution method: The presented program package solves the time-dependent Schrödinger equation with the wave function represented as sum over configuration products using an 8th-order adaptive step size Runge-Kutta ordinary differential equation (ODE) solver. The software can be extended by supplementing modules on the existing infrastructure.
Online veröffentlicht: 23 October 2024
Gesehen am 10.04.2025